Contesting Money: society, public policy, and the state in Hungary, 1945–1958 - Radi, Szinan (2023)
The thesis uses the state (chartalist) and credit theories of money to gain new insights into changing relations between ordinary citizens and the Hungarian postwar state between 1945 and 1958. The study focuses on the means (taxes, bonds, credits, the lottery), methods (propaganda, wage and price policy), and implications (price levels, purchasing power) of public finance. The thesis argues that the Hungarian postwar state was financially more vulnerable than previously assumed in historiography. Money was a constant point of contestation between regime and society during the period in question. It was both a measure of quality of life and a crucial legitimising and delegitimising force. Even during the most repressive Stalinist years, citizens counteracted state power and questioned the forint’s value, the course of public policy, and the state’s fiscal authority inflicted upon them often by turning the disorganised planned economy and communist bureaucracy to their advantage. The thesis contributes to the burgeoning socio-economic historiography of socialism by offering a novel and dynamic view on the interrelation of political and socio-economic change in postwar Hungary. Moreover, the study’s empirical assessment of money in socialism contributes to recent debates on the social function of money in the social sciences. The thesis relies on unused primary evidence sourced from Hungarian archives. It builds on party and ministerial reports on policy design and implementation, ‘mood reports’ of workers’ public opinion, personal letters, complaints, petitions, and private ‘proposals’ as well as interviews conducted with Hungarian émigrés during the early Cold War. In doing so, the thesis shows that due to citizens’ everyday experience with money as well as interpretation of and feedback on public policy, political, social, and economic structures developed in an interplay in the analysed period.